Studies on Al-Ni-Fe decagonal quasicrystalline alloy prepared by mechanical alloying - Yadav T.P.; Mukhopadhyay N.K.; Tiwari R.S.; Srivastava O.N. (My University, 2025)
Decagonal quasicrystalline Al70Ni24Fe6 powder was produced by mechanical alloying of the elemental powders followed by annealing. A high-purity elemental powder mixture of 70 at.% Al, 24 at.% Ni and 6 at.% Fe was mechanically milled for various times up to 100 h and annealed at 750C for 40 h. The powders milled for 100 h upon annealing showed formation of 200-300 nm size decagonal phase grains as the major component along with minor amounts of Al3Ni2 (3) and B2-type phases. The formation of decagonal phase and related crystalline phases was confirmed using the X-ray diffraction, scanning electron microscopy, transmission electron microscopy and energy dispersive X-ray microanalysis techniques. It is interesting to note that the decagonal phase did not form directly after milling. Subsequent annealing is required for the formation of decagonal quasicrystalline phase.